(untitled) (Archives of Criminology, 1984)
1. The idea of family jurisdiction is not new, yet it continues to raise animated discussion and controversy. Family courts which exist in many countries have miscellaneous and frequently rather narrow competence. Elsewhere, experiments have been made with family courts for many years now, consisting in taking observations of the works of a few family courts, the traditional orgnization of jurisdiction maintained in the entire country. The family jurisdiction, enforced in Poland on January 1st, 1978, was introduced in the entire territory, the competence of family courts outlined most broadly: all cases directly connected with family relations (affiliation of a child, alimony, nullification and dissolution of a marriage, adoption, limitation, suspension and deprivation of parental authority, institution of legal protection, etc.), cases connected with penal acts committed by juveniles, cases of compulsory treatment of alcoholics in closed hospitals, and offences against family, guardianship, and the youth, fell under competence of family courts. Family courts which are departments of district courts, have assembled nearly half of the cases coming in a district court. At the same time, cases have been divided between the judges basing on the territorial principle: every judge hears all kinds of cases coming in from the territory he has been assigned. This way, all cases essentially connected with the functioning of a given family were always to be judged by the same judge. The broad competence of a family judge and the fact that he heard all cases concerning the members of a given family was to create conditions in which all problems appearing within that family would be treated on a broad basis in every case, to ensure that each particular pronouncement concerning that family be compact and complementary, to guarantee the correctness of decisions owing to the knowledge of the whole of conflicts which occur in that family, and to make preventive activities broader and deeper. The creation of family courts caused the liquidation of juvenile courts, all their cases having passed to the family courts, as well as the transference of a considerable part of cases heard before by civil courts and a small number of cases from criminal courts. Such a far-reaching reform of organization of common jurisdiction has justified the study of the effects of introduction of family courts, the more so as juvenile courts played an important part in the system of preventive measures against delinquency and other forms of social maladjustment. Therefore, it was the aim of the study to find out if family courts realize their function in practice, and what are the factors that determine difficulties or irregularities in case the courts fail totally or partially to fulfill their object. The study embraced various sources of information about the functioning of family courts, i.e., first of all, statistical data on the jurisdiction in cases which now come within the scope of family courts from two periods: before and after they had been transferred to the family courts (years 1976-1977 and 1978-1981). Another extremely important source of information about the functioning of family courts was the analysis of cases of particular kind judged by juvenile, civil, and criminal couits, and then by family courts. Among the cases which provided a particularly great amount of information as to the way in which family courts fulfilled the goal they were planned to fulfill, were divorce suits, limitation of parental authority, penal acts of juveniles, and criminal cases of offences against family, guardianship, and the youth. Such cases require well-prepared materials before they are examined, comprehensive study of particular legal problems from the point of view of the interest of the family, first of all children that are brought up in it, and finally (apart from divorce suits) active execution of the sentence, as the method of execution determines the results of the entire preceding activity of the court. A detailed study was made of a standard sample of cases now investigated by 8 family courts - small, medium, and large, each of the 4 family courts created on January 1st, 1978, matched with one of the 4 family courts which had been functioning before that day as experimental courts. In this way comparison could have been made between the functioning of new family courts and those which had been working for some years to find out if the lenght of the period of work of the family court contributed to eliminating of various mistakes and dificiencies resulting from lack of experience during the first years of work of the family court. The standard of work of the "new" family courts emerging from the analysis of cases was also compared with that of juvenile courts, civil courts, and criminal courts which had been departments of the same district courts, by way of analysis of the same kind of cases judged before the reform of jurisdiction. This comparison was to provide information about changes which took place in preliminary proceedings, setencing, and execution of sentences, after family courts had taken over the cases which had been investigated before by other departments of district courts. Another source of information was the examination on the spot of the conditions of work of the 8 family courts the files of which had been analysed, including their staff, the system of social probation officers, the number of different duties imposed, and the power to execute decicions. Finally, the opinion on family courts was asked of family judges themselves, of professional probation officers of these courts, and of solicitors, whose experience in appearing before different courts in cases of the same kind seemed particularly valuable. A questionnaire examination also included the family judges who had judged in juvenile, civil, and criminal courts before the jurisdiction reform, so as to define their attitudes and opinions as regards various problems of family life. The aim of the questionnaire was to find out any differences between the attitudes of former juvenile court judges in comparison with other judges working subsequently in family courts. 2. The analysis of statistical data concerning the 6-year period (including 4 years after family jurisdiction had been introduced) did not reveal any symptomatic difference which could be related to the creation of family courts. As regards divorce suits, for instance, neither the percentage of cases discontinued due to the reconciliation of the parties increased, not that of dismissed cases; in cases concerning parental authority, the structure of decisions did not change; in cases of penal acts committed by juveniles but a small increase of less radical sentences was noticed; finally, as regards cases of offences against family, guardianship, and the youth, the only change was a slight reduction of the number of sentences to the penalty of deprivation of liberty without conditional suspension of execution in favour of limitation of parental authority. The results obtained through a detailed analysis of court files of cases formerly heard by juvenile, civil, and criminal courts were much the same as regards the contents of issued decisions. Nevertheless, in some spheres of activity of family courts some favourable changes occurred; unfortunately they were accompanied by a considerable regress in other spheres. In particular, family courts investigated the situation of children of divorcing parents more precisely than the civil courts, but on the other hand they neglected material problems, less frequently adjudging alimony amounting to a sum higher than demanded, less frequently deciding ex officio as to the means of using a common appartment by the divorced parties and adjudging eviction from the appartment of the party who particularly grossly disturbed the family peace. In all cases where the court’s decision should be properly executed by the family court machine, a considerable deterioration of the way of execution took place. This resulted both from the lack of adequate interest in this problem on the part of family judges who were engaged mostly in jurisdiction, and from remissness of professional probation officers who were also burdened with many other tasks and whose work was supervised by family judges but in a minimal degree. In spite of their contact with many kinds of cases, family judges showed little interest in prevention. It was interesting to find out that also the former juvenile judges who had been accustomed to give a lot of attention to various preventive activities, now did not differ by any means in this respect from the former civil and criminal judges. Also the functioning of the "old" family courts was by no means superior to that of the "new” ones, and it was even inferior in some spheres - therefore, the standard of work of the courts was determined by other factors and not by the lack of experience. The analysis of decisions from the point of view of complexity of their approach to the whole of the problems existing within a given family gave no evidence as to any differences between decisions in the same kinds of cases issued by family courts on the one hand, and juvenile, civil, and criminal courts on the other. Also the anticipation that decisions of family courts would be more compact and complementary to each other if several different cases of members of the same family would be heard by the same court, came true but to a minimal extent. Firstly, the percentage of families towards which at least 2 decisions had been issued by a family court during its period of existence was considerably low, amounting to 25 per cent of families ever included in any legal proceedings. Even in the case of those family courts which had been functioning for 7 years, the percentage in question was not high, amounting to 32 per cent. Secondly, in spite of the principle of territorial division of cases among the judges, only in half of cases, all suits concerning a given family were heard by the same judge. Thirdly, due to the nature of a considerable number of cases, the material gathered for them during the proceedings was of no importance as regards the way of examination and the essence of decision issued in the next case (this concerns first of all suits for alimony). Eventually, only in every seventh case both the same judge had heard the former case as well as the present one, and in the former case material had been gathered which was valuable for the better knowledge of the family and the more relevant judgement. It should also be mentioned that in the case of many of the decisions, there was considerable probability that the verdict sentences would have been similar, had they been adjudged by another judge of the same court, or of civil or criminal court. Therefore, it was impossible to ascertain that the creation of family courts had considerably contributed to a greater complexity, compactness, and complementariness of judgements. The opinions on the functioning of family courts gathered from judges, probation officers, and solicitors have confirmed a number of remarks made during the analysis of court files and the direct examination of the conditions of work of the selected family courts. In spite of the fact that the very idea of creating family courts has been estimated favourably by the majority of the examined persons (62 per cent), a considerable part of them pointed to the following defects: too wide range of tasks of family courts, the resulting overwork which hindered adequate preventive activities, the domination of jurisdiction as compared with other tasks of the family court. One third of the respondents could not see any advantage in the creation of family courts. Half of them was of opinion that the introduction of family courts failed to increase the protection of children and the youth against demoralization (this was most frequently the opinion of the family judges themselves). The second questionnaire, concerning opinions and attitudes of family judges, revealed the statements of the former juvenile judges concerning family and its problems to be more complete and definite as compared with statements of the former civil and criminal judges, and to take into consideration more frequently the psychological, pedagogical, social in its broadest sense, and even medical, aspects of these problems. One should, however, bear in mind that, as revealed by the analysis of files, no evidence was found of better work of the former juvenile judges as compared with other family judges. In the final part of the present article an attempt was made to draw conclusions from the results of the study. Having discussed different possible variants of changing the competence of family courts, a definite model of a family court was suggested, characterized by a different internal structure, narrowed competence and a better defined position in the system of prevention of social maladjustment of children and the youth.